2019
DOI: 10.1001/jamanetworkopen.2019.7063
|View full text |Cite
|
Sign up to set email alerts
|

Political Determinants of Population Health

Abstract: There is growing awareness of the association of highly racialized political discourse with health behaviors and, ultimately, health outcomes. 1 In this context, the study by Gemmill and colleagues 2 finding a significant increase in preterm births among Latina women following the 2016 US presidential election adds novel information to our understanding of the health impact of political events. Using a conservative interrupted time series analysis, they reported that there were 3.2% to 3.6% more preterm infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A related literature focuses on the consequences of political polarization for health behaviors (e.g., Iyengar et al 2019 andMontoya-Williams andFuentes-Afflick 2019). Party affiliation is correlated with physician recommendations on politicized health procedures, enrollment in government exchanges created under the Affordable Care Act, beliefs in the safety of vaccines, and hurricane evacuations (Hersh and Goldenberg 2016;Lerman et al 2017;Sances and Clinton 2019; controls for differential risk exposure or costs of social distancing (e.g., Economist 2020; Andersen 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A related literature focuses on the consequences of political polarization for health behaviors (e.g., Iyengar et al 2019 andMontoya-Williams andFuentes-Afflick 2019). Party affiliation is correlated with physician recommendations on politicized health procedures, enrollment in government exchanges created under the Affordable Care Act, beliefs in the safety of vaccines, and hurricane evacuations (Hersh and Goldenberg 2016;Lerman et al 2017;Sances and Clinton 2019; controls for differential risk exposure or costs of social distancing (e.g., Economist 2020; Andersen 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A related literature focuses on the consequences of political polarization for health behaviors (e.g., Iyengar et al 2019 andMontoya-Williams andFuentes-Afflick 2019). Party affiliation is correlated with physician recommendations on politicized health procedures, enrollment in government exchanges created under the Affordable Care Act, and beliefs in the safety of vaccines (Hersh and Goldenberg 2016;Lerman et al 2017;Sances and Clinton 2019;Trachtman 2019;Krupenkin 2018;Suryadevara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis by the U.S. Centers for Disease Control found that much of the difference between U.S. and European infant mortality rates was associated with the higher prevalence of preterm birth in the United States [4]. Preterm birth is the most common contributor to infant mortality in highly industrialized nations and is causally linked with chronic and acute psychosocial stressors facing expectant mothers [5] and political determinants of health [6].…”
Section: The Us Paradox In Infant and Maternal Healthmentioning
confidence: 99%